ASPECTS OF GREEN MARKETING, PRODUCTS, PRICES, AND BUYING INTEREST AT SUPER INDO OUTLETS - Sukoco, Andreas Ari; Herdioko, Jonathan; Krisanta, Brigitta Evelyn (Archives of Business Research, 2022)
Green marketing is basically a social marketing concept that protects and builds consumer welfare by paying attention to environmental sustainability. In the business context, the green marketing aspect is starting to become an aspect that is used as the basis for showing the advantages of a business. This study aims to see how green marketing moderates the effect of product and price on consumer buying interest. The aspects studied in this study include product aspects, price aspects, green marketing aspects and their influence on buying interest. The study was conducted in Yogyakarta with random sampling of Super Indo consumers. Field data collection is carried out in the period from May to July 2021. Data collection is carried out by distributing questionnaires with validity and reliability tests first. Data analysis was carried out using the Regression-Moderation model with product and price aspects as independent variables. Aspects of buying interest as an independent variable, while the green marketing variable as a moderating variable. The results of this study indicate that product and price aspects in general still have an effect on consumer buying interest. Meanwhile, an understanding of green marketing has a significant influence in moderating the relationship between products and consumer buying interest in Super Indo Supremarket retail.